MANAJEMEN JARINGAN KERJA SAMA DI MA MA’ARIFMINHAJUT-THOLABAH KEMBANGAN KECAMATAN BUKATEJA KABUPATEN PURBALINGGA - Kharis (CV. Amerta Media, 2017)
Cooperative network management is an effort to establish relationships with various parties, both private institutions and government agencies in order to remain able to survive in the emerging world of education competition in the future and improve the quality and quantity of education quality in public. In this case the cooperation network built by MA Ma'arif MinhajutTholabah Kembangan in the form of Dakwah Field Practice program, where the program is intended as a school strategy to survive in the competition of education world. While to launch a program can not run only one organization or institution but also required various parties for the goals and ideals of a program can run smoothly in accordance with what is expected. Based on these problems then there are problems that become the principal in this research is how the process of network management cooperation and what efforts are done in improving network cooperation in MA Ma'arif Minhajut-Tholabah Kembangan. The result of this research shows that the management of cooperation network in MA Ma'arif Minhajut-Tholabah Kembangan Bukateja Sub-district Purbalingga District aims to improve the quality and quantity of schools with the cooperation network as a recognition strategy or show its existence to the general public. In the implementation through the stages of planning, organizing, implementation and supervision as well as strategies to improve the network of cooperation which is all a process of application in the field Dakwah Practice Program.Keywords: Network Management Cooperation